FAKTOR-FAKTOR YANG MEMENGARUHI AGRESIVITAS PAJAK - Tanjung, Geraldio; Dewi, Sofia Prima (Jurnal Paradigma Akuntansi, 2024)
This study aims to determine the factors that influence tax aggressiveness in the mining industry listed on the Indonesia Stock Exchange during 2018-2020. This study uses a descriptive research design with purposive sampling method. There are 13 samples with a total of 39 data mining companies. This study uses the Economical Views 12 Student Version application. Data processing techniques using multiple regression analysis. The results of this study indicate that profitability has a negative effect on tax aggressiveness, firm size and managerial ownership have no positive effect on tax aggressiveness and leverage does not. negative effect on tax aggressiveness. With this research, it is hoped that it can improve the company's performance and can add insight in terms of tax aggressiveness. Companies can also consider legally tax aggressiveness to reduce the company's tax burden.